Biomaterial-based drug delivery systems in the treatment of inner ear disorders - Hong Cheng; Bin Zhang; Pei Jiang; Menghui Liao; Xin Gao; Dongyu Xu; Yusong Wang; Yangnan Hu; Huan Wang; Tingting Liu; Renjie Chai (Journal of Nanobiotechnology)
Abstract Inner ear disorders are among the predominant etiology of hearing loss. The blood-labyrinth barrier limits the ability of drugs to attain pharmacologically effective concentrations within the inner ear; consequently, delivering drugs systemically is insufficient for effectively treating inner ear disorders. Hence, it is imperative to create efficient, minimal or non-invasive methods for administering drugs to the inner ear. However, the development of such a system is hindered by three main factors: anatomical unavailability, the lack of sustained drug delivery, and individual variability. Advances in biomaterials technology have created new opportunities for overcoming existing barriers, offering great hope for the effective treatment of inner ear disorders. Hydrogel- and nanoparticle-based drug delivery systems can carry drugs to targeted designated anatomical locations in the inner ear for long-term, sustained release. Furthermore, a range of devices, including microneedles, micropumps, and cochlear implants, when paired with biomaterials, enhance the delivery of drugs to the inner ear, making the treatment of inner ear disorders more effective. Therefore, biomaterial-based drug delivery systems offer the possibility for extensive clinical uses and promise to restore hearing to millions of patients with inner ear disorders.